Research on the Impact of Carbon Tax on CO2 Emissions of China’s Power Industry - Yue Yu; Zhi-xin Jin; Ji-zu Li; Li Jia (Journal of Chemistry)
Based on the TIMES model, a system for CO2 emission reduction in China’s power industry is built in this paper. Four scenarios including different carbon tax levels are set up, simulating the CO2 emissions of China’s power industry in 2020–2050 by using scenario analysis method. The power consumption demand, primary energy consumption structure, CO2 emission characteristics, emission reduction potential, and cost of different carbon tax levels are quantitatively studied. In combination with the impact on China’s macroeconomy, the carbon tax level corresponding to the best CO2 emission reduction effect of China’s power industry is obtained, aiming to provide key data and a theoretical basis for China’s low-carbon development as well as the optimization and adjustment of global power production system. The results show that with the development of economy and society in the future, China’s power consumption demand will increase year by year, while the primary energy consumption of the power industry will maintain a rapid growth. The power industry still relies heavily on fossil energy, which will cause great pressure on China’s economic development and ecological environment. Carbon tax will have an important impact on the primary energy supply structure of China’s power industry, and renewable energy can be developed in different degrees. CO2 emissions will be significantly reduced, reaching the peak value during 2030–2040 in China’s power industry. The medium carbon tax level (TAX-2) set in this paper can meet the requirements of both CO2 emission reduction effect and cost in the power industry, with the most elastic impact on the national economy and the smallest GDP loss, which can be used as an effective environmental economic policy tool.